Exploring the therapeutic potential of baicalin against MCF-7 breast cancer cells: biochemical, in vitro, and computational perspectives - Ali, Adil; Upadhyay, Tarun Kumar; Al-Keridis, Lamya Ahmed; Alshahrani, Mohammad Y.; Alshamamri, Nawaf; Saeed, Mohd (Frontiers in Pharmacology, 2026)
BackgroundBaicalin (BA), a flavonoid extracted from the dried roots of Scutellaria baicalensis, is well known in traditional Chinese medicine (TCM) for its anti-apoptotic, anti-inflammatory, and antioxidant activities. However, its therapeutic potential in breast cancer needs to be evaluated systematically.MethodsIn this study, BA was isolated by probe sonication, bath-assisted sonication, and maceration. Chemical and structural characterisation was done by UV–VIS, Fourier-transform infrared spectroscopy (FT-IR), high-performance thin-layer chromatography (HPTLC), high-performance liquid chromatography (HPLC), liquid chromatography–mass spectrometry (LC–MS), X-ray diffraction (XRD), and nuclear magnetic resonance (NMR), while morphological and physicochemical attributes were evaluated by scanning electron microscopy (SEM), zeta size, and zeta potential analysis. Antioxidant activity was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric-reducing antioxidant power (FRAP), ABTS, reducing power, and H2O2 scavenging assays. Total flavonol, flavonoid, and phenolic contents were measured, and biocompatibility was examined through a haemolysis assay. Anticancer activity was evaluated in vitro in MCF-7 breast cancer cells through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), neutral red uptake (NRU), DCFH-DA, staining assays (Hoechst, propidium iodide (PI), LysoTracker, MitoTracker, JC-1, acridine orange/ethidium bromide (AO/EtBr)), and wound healing assay. Mechanism investigations were carried out using network pharmacology, docking, and 500 ns molecular dynamics simulations.ResultsBA possessed good antioxidant activity and biocompatibility. Phenolic (99.9 ± 0.27 mg/g GAE), flavonoid (80.4 ± 2 mg/g QE), and flavonol (79.4± 2 mg/g QE) contents were concentration-dependent. BA revealed strong cytotoxicity towards MCF-7 cells (IC50 = 160 μg/mL) compared to 5-fluorouracil (IC50=410 μg/mL), whereas it demonstrated low toxicity towards normal fibroblasts (IC50=2 mg/mL). Cell-based assays showed induction of apoptosis, ROS production, mitochondrial and lysosomal disruption, and inhibition of cell migration. Docking and simulations also demonstrated stable binding with carbonic anhydrase IX (CA9), dihydrofolate reductase (DHFR), and matrix metalloproteinase 1 (MMP1).ConclusionBA demonstrates strong antioxidant and selective anticancer activity with multi-target potential, supporting its promise as a natural therapeutic candidate for breast cancer.